Parallel and serial mediation analysis between pain, anxiety, depression, fatigue and nausea, vomiting and retching within a randomised controlled trial in patients with breast and prostate cancer - Charalambous A.; Giannakopoulou M.; Bozas E.; Paikousis L. (BMJ Publishing Group, 2022)
Objective Cancer treatment is a particularly stressful period for the patient. The reasons vary and include fear of treatment outcome as well as treatment induced side effects. The patient frequently experiences simultaneously various side effects resulting in a diminishing of the patient's health-related quality of life (HRQoL). The study provides evidence on the co-occurrence and inter-relations between pain, anxiety, depression and fatigue in patients with breast and prostate cancer. Design This paper presents a secondary analysis of the data from a randomised control trial designed to test the effectiveness of guided imagery and progressive muscle relaxation on pain, fatigue, anxiety and depression. Non-parametric bootstrapping analyses were used to test the mediational model of anxiety, fatigue and depression as parallel mediators of the relationship between pain and HRQoL. Setting The study was undertaken at the home setting. Participants In total 208 patients were included in the study (assigned equally in two groups), referred at the outpatient clinics of the three participating cancer care centres. Results The three mediators fully mediate the relationship between pain and HRQoL indirect effect (IE overall =-0.3839, 95% CI: Lower limit (LL)=-0.5073 to upper limit (UL)=-0.2825) indicating that patients with increased pain are likely to have higher levels of anxiety, fatigue and depression. Gender significantly moderated the mediational effect of Fatigue Index of Moderated Mediation (IMM=-0.2867 SE=0.1526, LL=-0.6127, UL=-0.0226) but did not moderate mediational effect of anxiety (IMM=-0.0709, SE=0.1414, LL=-0.3459, UL=+0.2089). The results show that the three mediators in a serial causal order fully mediate the relationship between pain and HRQoL (IE overall =-0.384, 95% CI: LL=-0.51 to UL=-0.284) and the ratio of the overall indirect effect to the total effect is 0.8315 (95% CI: LL=0.5683 to UL=1.1718). Conclusion This work provides evidence that targeting fatigue, anxiety and depression may have a meaningful effect on pain as a related symptom and potentially have a positive impact on HRQoL of patients with breast and prostate cancer.